A COMPARATIVE STUDY OF VIRECHANA KARMA AND BASTI KARMA IN AMAVATA W.S.R. TO RHEUMATOID ARTHRITIS (AYUSHDHARA, 2019)
Amavata is a Kapkavatavyadhi affecting people in the Madhyamaavasta. The disease is obtained by the involvement of Ama and Vata, characterized by Ruja and Shotha in Sandhisthanas. In this study the aims and objectives are to evaluate the effect of Nittyavirechana in Amavata, To evaluate the additive efficacy of Yogabasti in Amavata and To evaluate the comparative effect of Nittyavirechana and Yogabasti in Amavata.This was a prospective comparative clinical trial. Patients were randomly distributed into 2 groups which are 15 patients receiving Nittyavirechana with Erandataila and another 15 patients received Yogabasti with Erandamooladikwathaniruha and BruhatsandhavaditailaanuvasanaResults in group A 6.66% patients had good, 73.33% patients had moderate and 20% patients had mild response to the treatment. In group B 40% patients had good response, 60% patients had moderate response to the treatment. There was considerable improvement subjective and objective parameters in both the groups but Yogabasti group got more beneficial effects.Nittyavirechana imparts Agnideepana, Vatanulomana and opens up the Srotas in the Shareera facilitating more nourishment and free movement of Vatadosha. Yogabasti is prime treatment for Amavata in turn plays vital role in correcting pathology of the disease and gives remarkable results.